2017
DOI: 10.1186/s12939-016-0499-1
|View full text |Cite
|
Sign up to set email alerts
|

Intragenerational social mobility and functional somatic symptoms in a northern Swedish context: analyses of diagonal reference models

Abstract: BackgroundResearch indicate that social class mobility could be potentially important for health, but whether this is due to the movement itself or a result of people having been integrated in different class contexts is, to date, difficult to infer. In addition, although several theories suggest that transitions between classes in the social hierarchy can be stressful experiences, few studies have empirically examined whether such movements may have health effects, over and above the implications of “being” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
147
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(176 citation statements)
references
References 51 publications
22
147
3
4
Order By: Relevance
“…For example, Luthar, Barkin, and Crossman () reported that for upper‐class students, ‘cutting back to lower paying jobs [than their parents] is not an option’ (p. 1534), and that these students are exposed to several risks (e.g., drug and alcohol use; cheating). The experience of downward mobility has also been shown to be associated with a low level of subjective well‐being (Nikolaev & Burns, ) and a high experience of somatic symptoms (e.g., headache, stomach ache, backache, Jonsson, San Sebastian, Hammarström, & Gustafsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Luthar, Barkin, and Crossman () reported that for upper‐class students, ‘cutting back to lower paying jobs [than their parents] is not an option’ (p. 1534), and that these students are exposed to several risks (e.g., drug and alcohol use; cheating). The experience of downward mobility has also been shown to be associated with a low level of subjective well‐being (Nikolaev & Burns, ) and a high experience of somatic symptoms (e.g., headache, stomach ache, backache, Jonsson, San Sebastian, Hammarström, & Gustafsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…In einer Studie von Bartley und Plewis [8] zu Langzeiterkrankungen, wie auch in einer Untersuchung von Hallqvist et al [9] zum Myokardinfarkt kristallisierte sich das gleiche Muster heraus: Berufliche Aufwärtsmobilität war mit geringeren Erkrankungsrisiken gegenüber einem Verharren in unteren sozialen Statusgruppen assoziiert, hatte jedoch einen weniger starken positiven Effekt wie der Verbleib in einer hohen Statusgruppe. Andere Untersuchungen fanden jedoch keine oder nur schwache Zusammenhänge für funktionelle somatische Symptome oder subklinische Atheriosklerose [10,11].…”
Section: Hintergrundunclassified
“…Die schlechtere Gesundheit sozialer Absteiger kann womöglich mit dem damit einhergehenden Statusverlust und den verbundenen gesundheitsschädigenden Auswirkungen erklärt werden. Diese Verschlechterung wird als negatives Lebensereignis wahrgenommen, oftmals begleitet von Machtlosigkeit, Verzweiflung und Unsicherheit [10]. Bei Aufsteigern kann hingegen vermutet werden, dass mobilitätsbedingte Veränderungen im Lebensumfeld mit Exklusion, Einsamkeit oder auch psychosozialem Stress verbunden sind und so negativ auf die Gesundheit wirken [10].…”
Section: Diskussionunclassified
See 2 more Smart Citations